Impacto de agroquímicos usados na lavoura de arroz irrigado sobre a qualidade da água de irrigação e na comunidade zooplanctônica - Reimche, Geovane Boschmann (2010)
Agrochemicals are intensely used on rice (Orysa sativa L.) paddy culture, and depending on their environmental persistence and toxicity they may contaminate water bodies and affect non-target organisms. Both herbicides and insecticides are recommended for use in rice culture in southern Brazil. This study aimed was divided into three different experiments, with the following aims: (i) to determine the persistence of the herbicides imazethapyr + imazapic (Only®), bispyribac-sodium, penoxsulan, clomazone, and quinclorac and of the insecticides carbofuran and fipronil in irrigation water; (ii) to investigate the effect of these agrochemicals on physical, chemical and biological water quality; and, (iii) to investigate the effects of these agrochemicals on the native zooplanktonic biota of rice paddy fields cultivated under the direct seeding system. The field experiment was carried out in Santa Maria (RS), at the Federal University of Santa Maria (UFSM), in crop years 2007/08 and 2008/09; in 9.7 x 7.6 m= 73.7 m2 plots separated by soil levees. The experimental design used was randomized blocks with three replications. The treatments applied were imazethapyr (75 g a.i. ha-1) + imazapic (25 g a.i. ha-1) (Only®), bispyribacsodium (50 g a.i. ha-1), penoxsulan (48 a.i. g ha-1), clomazone (600 g a.i. ha-1), quinclorac (375 g a.i. ha-1), carbofuran (400 g a.i. ha-1) and fipronil (37.5 g a.i. ha-1) as well as a control block. In Experiment I, the agrochemicals persistence decreased in the following order: quinclorac > bispyribac-sodium = penoxsulan > carbofuran > imazapic > imazethapyr = fipronil > clomazone, detected for 84, 60, 60, 42, 39, 28, 28 e 25 days, respectively, (means of crop years 2007/08 and 2008/09). Quinclorac shows the greatest dissipation time (DT50) with 15.4 days, whilst clomazone exhibited the smallest DT50 value, 1.9 days. On Experiment II, results show that the isolated application of the herbicides and insecticides tested did not result in noticeable water quality alteration when compared to the control treatment. In general, physical, chemical and biological parameters remained below the values recommended by the environmental agencies used as reference for this study. In Experiment III, results indicated that Rotifers had the highest abundance in the zooplankton community, with Polyarthra as the most abundant genus; it was also concluded that the agrochemicals had little effect over the Rotifera and Copepoda groups (adult and nauplii).